Role of (18)F-FDG PET Scan in Rheumatoid Lung Nodule: Case Report and Review of the Literature - Chhakchhuak, Christine L. (Hindawi Publishing Corporation, 2013)
Flourine-18 fluoro-2-deoxy-glucose ((18)F-FDG) positron emission tomography combined with computed tomography (PET/CT) is a useful test for the management of malignant conditions. Inflammatory and infectious processes, however, can cause increased uptake on PET scanning, often causing diagnostic dilemmas. This knowledge is important to the rheumatologist not only because of the inflammatory conditions we treat but also because certain rheumatic diseases impose an increased risk of malignancy either due to the disease itself or as a consequence of medications used to treat the rheumatic diseases. There is an increasing body of evidence investigating the role of PET scans in inflammatory conditions. This paper describes a patient with rheumatoid arthritis who developed pulmonary nodules that showed increased uptake on PET/CT scan and reviews the use of PET scanning in the diagnosis and management of rheumatoid arthritis.